Clinical Evaluation of Vyoshadi Guggulu and Haritaki Churna in the Management of Dyslipidemia - Hemang Ragvani, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Clinical Evaluation of Vyoshadi Guggulu and Haritaki Churna in the Management of Dyslipidemia